MODEL OF MOSQUE AS ZAKAT MANAGEMENT CENTER - Moh. Nurul Qomar; M. Chamim; Makrufah Hidayah Islamiah (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
The establishment of the National Zakat Agency (BAZNAS) is a form of the seriousness of the government in the management of zakat. According to Law No. 23/2011 on Zakat Management, BAZNAS can be assisted by Amil Zakat Institution (LAZ) in the management of zakat. The government manages zakat professionally and transparently. The serious government in this case is not without reason. This research tries to explore the role of zakat in using zakat not only as mahdhah worship but also as a social instrument. For that, we need a model of the mosque as a center for managing zakat.This research method puts forward the library research approach because it includes qualitative research. The analysis uses a content analysis approach. The mosque model as a center for managing zakat requires a concept comprising four economic pillars of the mosque, The concept of a mosque as an integrated zakat manager requires 4 economic pillars of the mosque namely (1) Foundation based on the basic principles of Islamic economy (2) Level I is the center of economic activity, (3) The Second Floor for the economic institutions of the people such as Sharia Banking, BMT (4) the Mosque itself as a fund repayment of economic activities and economic institutions.